Ontological Awareness in Food Systems Education - Dring, Colin C.; Čajková, Teresa; Mendes, Wilson; Stein, Sharon; Valley, Will; Clegg, Daniel J. (Frontiers in Sustainable Food Systems, 2022)
We observe efforts in Sustainable Food Systems Education and Critical Food Systems Education literature to employ education in ways that seek social and environmental transformation of food systems. Here, we argue that forms of food systems education that are disconnected from awareness of their ontological roots are destined to reproduce the same food systems with the same consequences for life on Earth. This theoretical paper invites discussions that unpack “habits of being” underpinning modern/colonial conceptualizations of food system issues, transformation efforts, and pedagogies. We note the risk of reinscribing, within food systems education, specific onto-epistemological norms and values that are the root of multiple crises facing food systems (separability, global capital, nation-states, humanism). Using the metaphor of the “house that modernity built,” we invite scholars, teachers, learners, and other practitioners to bring explicit attention to how the ontology of Western modernity arises in discourses on food systems and is reproduced through food systems education. We begin by describing this ontological position and its dominance, situating how contemporary transformations in food systems education neglect ontological foundations, and enumerating a set of harms arising from this disavowal. As a beginning, we suggest that fields related to food systems are a compelling place to interrupt a habit of being that denies and disavows even the presence of ontological positions. Food systems educators within postsecondary institutions are entreated to develop their analyses and pedagogical approaches toward a more just and sustainable future that denaturalizes harmful and falsely universalized ontological foundations.